Pengemasan Informasi pada Konten Instagram dalam Mengkomunikasikan Pesan Kebencanaan - Dandi Putra Nugraha; Yulianti (Bandung Conference Series: Communication Management, 2023)
Abstract. Information technology advances that make it easier for humans to carry out social activities, have an impact on the attitudes and social behavior of Indonesian people, especially users of social media, such as the spread of hoax (fake) news. This study describes the process of packaging Instagram social media information carried out by Jabar Saber Hoaks in distributing Instagram social media content. The research methodology in this research is quantitative research with a descriptive approach. The information packaging model is used as the basis for the theory and concepts in this study, which was put forward by Sturges (1994): instruction information, adjusting information, and internalizing information in information packaging by @jabarsaberhoaks. data collection in this study used interviews, observation, and literature study. The results of this study were, (1) Instruction information, the Jabar Saber Hoaks team conveyed information with appeals and self-protection in evacuating the public from the spread of hoax news in the midst of a natural disaster. (2) adjusting information, the Jabar Saber Hoaks team conveys information in a persuasive, educative and recreational way in the recovery effort amid natural disaster situations. (3) internalizing information, Jabar Saber Hoaks packages information by increasing the quality of reputation in the provision and service of information. Therefore the packaging of information carried out by Jabar Saber Hoaks can be found through Instagram content @jabarsaberhoaks, one of which is in delivering instructional information that can be assessed fast, actual, and consistent, namely by delivering messages of self-protection and messages of appeal to anticipate the spread of hoax news. Besides that, aspects of adjusting information and internalizing can also be found in @jabarsaberhoaks content. Abstrak. Kemajuan teknologi informasi yang memudahkan manusia untuk menjalankan aktivitas sosial, berdampak terhadap sikap dan perilaku sosial masyarakat Indonesia terutama pengguna media sosial, seperti penyebaran berita hoaks (palsu). Penelitian ini menjabarkan proses pengemasan informasi media sosial Instagram yang dilakukan oleh Jabar Saber Hoaks dalam mendistribusikan konten media sosial Instagram. Metodologi penelitian dalam penelitian ini ialah penelitian kuantitatif dengan pendekatan deskriptif. Model kemasan informasi digunakan sebagai landasan teori dan konsep dalam penelitian ini, yang dikemukakan oleh Sturges (1994): instruction information, adjusting information, dan internalizing information dalam pengemasan informasi oleh @jabarsaberhoaks. Pengumpulan data pada penelitian ini menggunakan wawancara, observasi, dan studi kepustakaan. Hasil dari penelitian ini yaitu, (1) Instruction information, tim jabar saber hoaks menyampaikan informasi dengan himbauan dan perlindungan diri dalam mengevakuasi masyarakat dari penyebaran berita hoaks di tengah situasi bencana alam. (2) adjusting information, tim Jabar Saber Hoaks menyampaikan informasi secara persuasif, edukatif, dan rekreatif dalam upaya pemulihan di tengah situasi bencana alam. (3) internalizing information, Jabar Saber Hoaks mengemas informasi dengan meningkatkan kualitas reputasi dalam penyediaan dan pelayanan informasi.Oleh karena itu pengemasan informasi yang dilakukan oleh Jabar Saber Hoaks yakni dapat ditemukan melalui konten Instagram @jabarsaberhoaks, yang salah satunya dalam menyampaikan instruction information dapat dinilai cepat, aktual, dan konsisten, yakni dengan penyampaian pesan perlindungan diri dan pesan himbauan untuk mengantisipasi penyebaran berita hoaks. Selain itu aspek adjusting information dan internalizing juga dapat ditemukan pada konten @jabarsaberhoaks.